Immigration – Socio-economical Implications. The Case of Romania - Silviu Neguţ; Luigi di Comite; Marius-Cristian Neacşu (Amfiteatru Economic Journal, 2010)
The purpose of this study is to initially identify, at an exploratory level, an immigration model in Romania, with a special focus on economic immigration. It is well known that Romania, although source country, on our continent (Spain, Italy, Belgium, France etc.), as well as on the American (Canada, U.S.A) or the Australian one, with a negative migratory balance rate, after joining the European Union, it will become in the near future a destination country, especially for ,,economic immigrants”. The natural population deficit with which Romania is currently confronted, the labour market imbalances (the low level of participation of the current population in the productive process and the high number of Romanians working abroad) and the experience of older European Union members support the idea. As such, the analysis of social and economical risks that rising immigration will bring on the Romanian society is rather interesting and the applicative uses reside in identifying risk management solutions, in the context of formulating specific policies for immigration management.
Keywords: J61; 330; immigration; foreign labour force; Romania; European Union